A ternary high-voltage lithium ion battery nonaqueous electrolyte and a lithium ion battery
Patent Information
- Application Number
- CN202210531543.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-17
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2042-05-17
AI Technical Summary
Traditional carbonate electrolytes have a narrow electrochemical window. As the voltage increases, the electrolyte decomposes, the positive electrode oxidation capacity increases, and metal dissolution, gas evolution, and material phase change lead to lithium-ion battery failure, which limits the development of high-voltage lithium-ion batteries.
The non-aqueous electrolyte used in ternary high-voltage lithium-ion batteries contains phosphorus sulfate compounds with specific structures, oxalate-type additives, and silane additives to form stable SEI and CEI films, optimize the performance of the electrolyte under high voltage, suppress decomposition and gas production, and improve safety and stability.
A low-impedance SEI film is formed under high voltage to suppress electrolyte decomposition, improve the cycle stability and thermal stability of the battery, and enhance the battery's energy density and safety performance.
Smart Images

Figure CN117117310B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, specifically to a ternary high-voltage lithium-ion battery non-aqueous electrolyte and the lithium-ion battery itself. Background Technology
[0002] With technological advancements, people's demands for the quality of their living environment are constantly increasing. Meanwhile, the environmental pollution caused by the depletion and consumption of fossil fuels is becoming increasingly serious, making the research and development of clean and renewable energy sources an urgent priority. Currently, a large number of new energy sources have been developed and utilized, such as solar, wind, tidal, and geothermal energy. However, these energy sources are limited in time and space, requiring appropriate conversion and storage before they can be used.
[0003] Lithium-ion batteries, as a green and environmentally friendly high-energy battery, are currently the most ideal and promising rechargeable batteries in the world. Compared with other batteries, they possess a series of advantages such as no memory effect, rapid charging and discharging, high energy density, long cycle life, and no environmental pollution. Therefore, they are widely used in small electronic devices such as laptops, cameras, mobile phones, and smartwatches. With the increasing demands on lithium-ion battery capacity from pure electric vehicles, hybrid vehicles, and portable energy storage devices, there is a growing expectation for the development of lithium-ion batteries with higher energy and power densities to achieve longer driving range and energy storage. Increasing the operating voltage can improve the energy density of lithium-ion batteries, but traditional carbonate electrolytes have a narrow electrochemical window. As the voltage increases, the electrolyte itself decomposes; furthermore, the increased oxidation capacity of the positive electrode under high voltage, along with significant metal dissolution, gas evolution, and material phase transitions, can lead to battery failure or even dangerous situations. These problems limit the development of high-voltage lithium-ion batteries. Therefore, it is necessary to develop high-performance, high-safety electrolytes that can withstand high voltage. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of the aforementioned background technology and provide a non-aqueous electrolyte for ternary high-voltage lithium-ion batteries and a lithium-ion battery thereof. The non-aqueous electrolyte for ternary high-voltage lithium-ion batteries of this invention, through optimized formulation and the combined effect of a unique combination of multiple components, enables the electrolyte system to possess both high energy density and high stability, which is beneficial for meeting the requirements of electrolyte cycling and storage performance under high voltage, while ensuring safety.
[0005] To achieve the objectives of this invention, the non-aqueous electrolyte for a ternary high-voltage lithium-ion battery comprises a non-aqueous organic solvent, an electrolyte lithium salt, and electrolyte additives. The additives include film-forming additives, oxalate-type additives, and silane-based additives. The film-forming additives include phosphorus-containing sulfate compounds, the structural formula of which is shown in formula (Ⅰ).
[0006]
[0007] The substituents R1, R2, and R3 are independently selected from alkyl, alkoxy, ester, alkenyl, alkynyl, fluoroalkyl, cyano, and isocyanate groups with 1 to 4 carbon atoms.
[0008] Furthermore, in some embodiments of the present invention, the phosphorus-containing sulfate compound is selected from at least one of the compounds shown in the following structural formulas:
[0009]
[0010] Furthermore, in some embodiments of the present invention, the mass percentage of the phosphorus-containing sulfate compound in the electrolyte is 0.05-1%, for example 0.2-1%.
[0011] Furthermore, in some embodiments of the present invention, the film-forming additive further comprises one or more of 1,3-propanesulfonate lactone (PS), fluoroethylene carbonate (FEC), vinylene carbonate (VC), and ethylene sulfate (DTD).
[0012] Preferably, in some embodiments of the present invention, the film-forming additive further comprises one or more of vinylene carbonate (VC) and ethylene sulfate (DTD).
[0013] More preferably, in some embodiments of the present invention, the film-forming additive further includes 0.4-0.6% by mass of vinylene carbonate (VC) or 0.4-0.6% by mass of ethylene sulfate (DTD) in the electrolyte.
[0014] Furthermore, in some embodiments of the present invention, the oxalate-type additive is selected from one or more of lithium difluorobis(oxalate) phosphate (LiDFOP), lithium difluorobis(oxalate) borate (LiDFOB), lithium tetrafluorobis(oxalate) phosphate (LTFOP), and lithium bis(oxalate) borate (LiBOB).
[0015] Preferably, in some embodiments of the present invention, the oxalate-type additive has a mass percentage of 0.4-1.2% in the electrolyte.
[0016] Furthermore, in some embodiments of the present invention, the silane additive is selected from one or more of tris(trimethylsilyl)phosphate (TMSP), tris(trimethylsilyl)borate (TMSB), and tris(trimethylsilyl)phosphite (TMSPi).
[0017] Furthermore, in some embodiments of the present invention, the silane additive is present in the electrolyte at a mass percentage of 0.1-2%, for example, 0.3-0.7%.
[0018] Furthermore, in some embodiments of the present invention, the electrolyte lithium salt is selected from one or more of lithium hexafluorophosphate (LiPF6), lithium bisfluorosulfonylimide (LiFSI), lithium bistrifluoromethanesulfonylimide (LiTFSI), lithium difluorophosphate (LiPO2F2), and lithium tetrafluoroborate (LiBF4).
[0019] Furthermore, in some embodiments of the present invention, the mass percentage of the electrolyte lithium salt in the electrolyte is 10-20%.
[0020] Furthermore, in some embodiments of the present invention, the non-aqueous organic solvent is selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and methyl ethyl carbonate (EMC).
[0021] Preferably, in some embodiments of the present invention, the non-aqueous organic solvent is ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), or methyl ethyl carbonate (EMC); more preferably, the mass ratio of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and methyl ethyl carbonate (EMC) is 20-30:7-13:15-25:40-50.
[0022] Furthermore, in some embodiments of the present invention, the high voltage refers to the upper limit cutoff voltage of the battery being 4.35-4.5V.
[0023] On the other hand, the present invention also provides a ternary high-voltage lithium-ion battery, the ternary high-voltage lithium-ion battery comprising a positive electrode, a negative electrode, a separator, and the aforementioned non-aqueous electrolyte of the ternary high-voltage lithium-ion battery of the present invention.
[0024] Furthermore, in some embodiments of the present invention, the active material of the positive electrode is a ternary NCM material; the material of the negative electrode is one or more of natural graphite, artificial graphite, lithium titanate, silicon-oxygen negative electrode, and silicon negative electrode.
[0025] Furthermore, in some embodiments of the present invention, the upper limit cutoff voltage of the lithium-ion battery is 4.35-4.5V.
[0026] Compared with the prior art, the advantages of the present invention include, but are not limited to:
[0027] (1) In the non-aqueous electrolyte of the high-voltage lithium-ion battery of the present invention, the functional groups contained in the phosphorus-containing sulfate compounds with specific structural formulas form a low-resistance SEI film at the negative electrode (the sulfate structure can increase the S content in the SEI film, improve ion mobility, optimize impedance, and reduce the damage to the negative electrode caused by lithium ion insertion / extraction); after optimizing the substituents, it can adapt to the high-voltage environment and form a stable CEI film at the positive electrode, inhibiting the decomposition of the electrolyte at the positive electrode (cyano group); at the same time, it optimizes the aqueous acid environment, inhibits the impedance growth during cycling and storage (isocyanate group), improves the battery storage performance, and reduces the internal resistance growth and gas generation during use; the introduction of the phosphate ester structure improves the non-flammability of the electrolyte and enhances the safety performance of the electrolyte. In this way, the cycle stability and thermal stability of the battery are comprehensively guaranteed.
[0028] (2) The high-voltage lithium-ion battery non-aqueous electrolyte of the present invention, through optimized formulation and combined with the combined effects of phosphorus sulfate compounds, oxalate additives, and borosilicate ester additives with specific structural formulas: the phosphorus sulfate additives form films on both the positive and negative electrodes, suppress gas generation, suppress the increase in impedance during cycling and storage, and improve the safety performance of the electrolyte; the oxalate additives play a film-forming role, while the phosphorus sulfate additives optimize the film impedance and suppress its gas generation side effects; the borosilicate ester additives improve the oxidation stability of EC and enhance the Li + Migration number, and thus comprehensively, ensures that high-voltage lithium-ion batteries have excellent cycle performance and storage performance, enabling the battery system to have both high energy density and high stability. Detailed Implementation
[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. Additional aspects and advantages of this invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. It should be understood that the following description is merely illustrative and not intended to limit the invention.
[0030] The terms “comprising,” “including,” “having,” “containing,” or any other variations thereof, as used herein, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.
[0031] The conjunction "composed of..." excludes any unspecified elements, steps, or components. If used in a claim, this phrase makes the claim closed, excluding materials other than those described, except for associated conventional impurities. When the phrase "composed of..." appears in a clause of the body of a claim rather than immediately following it, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0032] When a quantity, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether the range is disclosed individually. For example, when the range “1 to 5” is disclosed, the described range should be interpreted as including the ranges “1 to 4”, “1 to 3”, “1 to 2”, “1 to 2 and 4 to 5”, “1 to 3 and 5”, etc. When numerical ranges are described herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within that range.
[0033] The singular form includes the plural objects of discussion, unless the context clearly indicates otherwise. "Optional" or "any one" means that the matter or event described thereafter may or may not occur, and the description includes both the possibility that the event occurs and the possibility that the event does not occur.
[0034] Approximate terms used in the specification and claims to modify quantities indicate that the invention is not limited to that specific quantity, but also includes acceptable modifications close to that quantity that do not alter the relevant essential function. Correspondingly, the use of "about," "approximately," etc., to modify a numerical value means that the invention is not limited to that precise value. In some instances, approximate terms may correspond to the precision of the instrument used to measure the value. In this application's specification and claims, scope definitions can be combined and / or interchanged, unless otherwise stated, these scopes include all subscopes contained therein.
[0035] The indefinite articles “a” and “an” preceding an element or component of this invention do not impose any limitation on the quantity (i.e., number of times) of the element or component. Therefore, “an” or “a” should be interpreted as including one or at least one, and the singular form of an element or component also includes the plural form, unless the quantity clearly refers only to the singular form.
[0036] Furthermore, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., described below refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms are not necessarily directed at the same embodiment or example. Moreover, the technical features involved in the various embodiments of the present invention can be combined with each other as long as they do not conflict with each other.
[0037] The structures and designations of the phosphorus-containing sulfate compounds in the embodiments and comparative examples of this invention are as follows:
[0038] The structural formula for M1 is:
[0039]
[0040] The structural formula for M2 is:
[0041]
[0042] The structural formula for M3 is:
[0043]
[0044] The structural formula for M4 is:
[0045]
[0046] The structural formula for M5 is:
[0047]
[0048] Example 1
[0049] Preparation of electrolyte: In an argon-filled glove box (oxygen content ≤1ppm, water content ≤1ppm), ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and methyl ethyl carbonate (EMC) were mixed uniformly in a mass ratio of 25:10:20:45 to obtain a mixed solution. Then, 12.5% of lithium hexafluorophosphate (LiPF6) and 0.5% of lithium difluorooxalate borate (LiDFOB) based on the total mass of the electrolyte were added to the mixed solution. Subsequently, 0.5% of phosphorus-containing sulfate compound M1, 0.5% of ethylene carbonate (VC), and 0.5% of tris(trimethylsilyl)borate (TMSB) based on the total mass of the electrolyte were added to the mixed solution, and the mixture was stirred until completely dissolved to obtain the electrolyte of Example 1.
[0050] Example 2-13
[0051] Examples 2-13 are also specific examples of electrolyte preparation. Except that the composition ratio of each component of the electrolyte is added as shown in Table 1, the other parameters and preparation methods are the same as in Example 1.
[0052] Comparative Examples 1-5
[0053] Comparative Examples 1-5 were identical to Example 1 except that the electrolyte components were added in the proportions shown in Table 1.
[0054] Table 1 Electrolyte composition of the examples and comparative examples
[0055]
[0056]
[0057] Note: The content of each component in lithium salt is the mass percentage in the electrolyte;
[0058] The content of phosphorus-containing sulfate compounds is the mass percentage in the electrolyte;
[0059] The content of each component in other additives is the mass percentage in the electrolyte;
[0060] The proportions of each component in the solvent are by mass.
[0061] Preparation of ternary lithium batteries:
[0062] The positive electrode active material NCM622, the conductive agent acetylene black, and the binder polyvinylidene fluoride were thoroughly mixed in an N-methylpyrrolidone system at a mass ratio of 95:3:2. The mixture was then coated onto aluminum foil, dried, and cold-pressed to obtain the positive electrode sheet.
[0063] The negative electrode active material artificial graphite, conductive agent super carbon black, thickener sodium carboxymethyl cellulose, and binder styrene-butadiene rubber are mixed evenly in a deionized water solvent system at a mass ratio of 95:1:2:2. The mixture is then coated onto copper foil, dried, and cold-pressed to obtain the negative electrode sheet.
[0064] A polyethylene base membrane is used, and a nano-alumina coating is coated on the base membrane to serve as a separator.
[0065] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide isolation. The cells are then wound to obtain a bare cell. The bare cell is placed in an outer packaging, injected with the prepared electrolyte, and undergoes processes such as encapsulation, formation, aging, secondary encapsulation, and capacity testing to obtain an NCM622 / graphite lithium-ion battery.
[0066] Lithium-ion battery performance testing
[0067] (1) Room temperature cycle performance test: At 25℃, the above ternary / graphite lithium-ion batteries were charged to 4.35V at 1C constant current and constant voltage, with a cutoff current of 0.05C, and then discharged to 3.0V at 1C constant current. The capacity retention rate at the 500th cycle was calculated after 500 charge / discharge cycles. The calculation formula is as follows:
[0068] Capacity retention rate at week 500 = Week 500 cycle discharge capacity / Week 1 cycle discharge capacity × 100%.
[0069] (2) High-temperature storage performance at 60℃: The above-mentioned ternary / graphite lithium-ion batteries were charged and discharged once at 1C at room temperature, with a cutoff current of 0.05C, and the initial capacity was recorded. Then, the batteries were fully charged at 1C constant current and constant voltage, and the initial thickness and initial internal resistance of the batteries were tested. The fully charged batteries were stored in a constant temperature environment of 60℃ for 14 days, and the thermal expansion rate was calculated. After the batteries cooled to room temperature for 6 hours, they were discharged at 1C to 3.0V, and the remaining capacity of the batteries was recorded. The remaining capacity rate of the batteries was calculated using the following formula:
[0070] Battery thermal expansion rate (%) = (thermal thickness - initial thickness) / initial thickness × 100%;
[0071] Battery capacity remaining rate (%) = Remaining capacity / Initial capacity × 100%;
[0072] Battery capacity recovery rate (%) = Recovered capacity / Initial capacity × 100%
[0073] (3) Self-extinguishing time test of non-aqueous electrolyte: The self-extinguishing time of the non-aqueous electrolytes for lithium-ion batteries prepared in Examples 1-13 and Comparative Examples 1-5 was tested. The raw material for the self-extinguishing time test was prepared into a batch of spheres with a radius of approximately 5 mm using glass wool. First, their mass was weighed and recorded. Next, the glass wool spheres were immersed in the corresponding non-aqueous electrolyte used in the preparation of the lithium-ion batteries for 30 seconds, and then weighed again. The difference in mass before and after immersion was the mass of the non-aqueous electrolyte absorbed by the glass wool spheres. Finally, the glass wool spheres were placed on a circular iron wire, ignited using a gas ignition device, and the time it took for the glass wool spheres to extinguish was recorded. The above data are recorded as follows:
[0074] Table 2 Battery performance of the examples and comparative examples
[0075]
[0076]
[0077] As can be seen from Examples 1-13 and Comparative Examples 1-5, the lithium-ion batteries using the electrolytes of Examples 1-13 exhibit better room-temperature cycling performance and high-temperature storage performance than the lithium-ion batteries of Comparative Examples 1-5. This is because the high-voltage lithium-ion battery non-aqueous electrolyte of the present invention, through optimized formulation and the combined effect of a unique combination of three components (containing phosphorus sulfate esters, oxalates, and silane additives): the phosphorus sulfate ester additives form films on both the positive and negative electrodes, suppressing gas generation, inhibiting the increase in impedance during cycling and storage, and increasing the flame retardancy of the electrolyte; the oxalate additives play a film-forming role, while the phosphorus sulfate ester additives optimize film impedance and suppress its gas generation side effect; the silica borate ester additives improve the oxidation stability of EC and increase the Li+ migration number.
[0078] It can generate stable CEI and SEI films inside the battery, reduce the electrolyte oxidation rate on the positive electrode surface under high voltage, reduce the increase in battery impedance, remove water and suppress acid, inhibit the side effects of lithium difluorooxalate borate, and prevent gas generation, thereby ensuring that high-voltage ternary-graphite batteries have long cycle life, excellent high-temperature storage performance and reliable safety.
[0079] Meanwhile, for phosphorus-containing sulfate compounds, when the amount added was too high (2%, Comparative Example 4), the cycling capacity decreased significantly. It is speculated that when too much of this compound is added, the film-forming effect is poor in the early stage, and the electrolyte can still interact with the positive electrode active site in large quantities during the later cycle, resulting in continuous deterioration of the film quality and ultimately leading to a rapid decrease in capacity. When the amount of phosphorus-containing sulfate compounds added was too low (0.05%, Comparative Example 5), the film-forming effect at the positive and negative electrode interface was slightly weak, the coating effect on the positive electrode active site was insufficient, the electrochemical performance was poor, and the improvement on the non-flammability of the electrolyte was also limited. Therefore, the optimal addition amount is 0.2%-1%.
[0080] Comparative Example 3 data shows that the formulation with only phosphorus sulfate compounds and lacking other additives has limited effect; while the capacity retention rates of Comparative Examples 1 and 2, which did not contain phosphorus sulfate compounds, were slightly lower after 500 cycles at room temperature compared to the examples, indicating that the interfacial film formed by the phosphorus sulfate compounds in combination with other film-forming additives and lithium salt additives in the electrolyte is superior and more stable, which can improve the cycle and storage performance of the battery. Meanwhile, comparing several phosphorus sulfate compounds with different substituents, the data shows that M3, M4, and M5 can form a low-impedance, high-quality CEI film, exhibiting better cycle performance and lower DCR; while M1 has a poorer overall performance.
[0081] Those skilled in the art will readily understand that the above description is merely an embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A non-aqueous electrolyte for a ternary high-voltage lithium-ion battery, characterized in that, The non-aqueous electrolyte of the ternary high-voltage lithium-ion battery comprises a non-aqueous organic solvent, an electrolyte lithium salt, and electrolyte additives. The additives include film-forming additives, oxalate-type additives, and silane-based additives. The oxalate-type additives are selected from one or more of lithium difluorobis(oxalato) phosphate (LiDFOP), lithium difluorobis(oxalato) borate (LiDFOB), lithium tetrafluorobis(oxalato) phosphate (LTFOP), and lithium bis(oxalato) borate (LiBOB), and the oxalate-type additives constitute 0.4-1.2% of the electrolyte by mass. The silane-based additives are selected from one or more of tris(trimethylsilyl) phosphate (TMSP), tris(trimethylsilyl) borate (TMSB), and tris(trimethylsilyl) phosphite (TMSPi), and the silane-based additives constitute 0.3-0.7% of the electrolyte by mass. The film-forming additives include phosphorus-containing sulfate compounds, which are selected from at least one of the compounds shown in the following structural formulas: 。 2. The non-aqueous electrolyte for a ternary high-voltage lithium-ion battery according to claim 1, characterized in that, The mass percentage of the phosphorus-containing sulfate compound in the electrolyte is 0.05-1%.
3. The non-aqueous electrolyte for a ternary high-voltage lithium-ion battery according to claim 1, characterized in that, The mass percentage of the phosphorus-containing sulfate compound in the electrolyte is 0.2-1%.
4. The non-aqueous electrolyte for a ternary high-voltage lithium-ion battery according to claim 1, characterized in that, The film-forming additive also contains one or more of 1,3-propanesulfonate lactone (PS), fluoroethylene carbonate (FEC), vinylene carbonate (VC), and ethylene sulfate (DTD).
5. The non-aqueous electrolyte for a ternary high-voltage lithium-ion battery according to claim 1, characterized in that, The film-forming additive also includes one or more of vinylene carbonate (VC) and ethylene sulfate (DTD).
6. The non-aqueous electrolyte for a ternary high-voltage lithium-ion battery according to claim 1, characterized in that, The film-forming additive also includes 0.4-0.6% by mass of vinylene carbonate (VC) or 0.4-0.6% by mass of ethylene sulfate (DTD) in the electrolyte.
7. The non-aqueous electrolyte for a ternary high-voltage lithium-ion battery according to claim 1, characterized in that, The electrolyte lithium salt is selected from one or more of lithium hexafluorophosphate (LiPF6), lithium bisfluorosulfonylimide (LiFSI), lithium bistrifluoromethanesulfonylimide (LiTFSI), lithium difluorophosphate (LiPO2F2), and lithium tetrafluoroborate (LiBF4).
8. The non-aqueous electrolyte for a ternary high-voltage lithium-ion battery according to claim 1, characterized in that, The mass percentage of the electrolyte lithium salt in the electrolyte is 10-20%.
9. The non-aqueous electrolyte for a ternary high-voltage lithium-ion battery according to claim 1, characterized in that, The non-aqueous organic solvent is selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and methyl ethyl carbonate (EMC).
10. The non-aqueous electrolyte for a ternary high-voltage lithium-ion battery according to claim 1, characterized in that, The non-aqueous organic solvent is ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), or methyl ethyl carbonate (EMC).
11. The non-aqueous electrolyte for a ternary high-voltage lithium-ion battery according to claim 10, characterized in that, The mass ratio of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and methyl ethyl carbonate (EMC) is 20-30:7-13:15-25:40-50.
12. The non-aqueous electrolyte for a ternary high-voltage lithium-ion battery according to claim 1, characterized in that, The high voltage refers to the upper limit cutoff voltage of the battery, which is 4.35-4.5V.
13. A ternary high-voltage lithium-ion battery, characterized in that, The ternary high-voltage lithium-ion battery includes a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte as described in any one of claims 1-12.
14. The ternary high-voltage lithium-ion battery according to claim 13, characterized in that, The active material of the positive electrode is a ternary NCM material; the material of the negative electrode is one or more of natural graphite, artificial graphite, lithium titanate, silicon-oxygen negative electrode, and silicon negative electrode.
Citation Information
Patent Citations
Non-aqueous electrolyte, and non-aqueous electrolyte cell using the same
CN103053060A
Lithium-ion battery electrolyte and lithium-ion battery containing same
CN111029653A
Non-aqueous electrolyte for high-voltage lithium ion battery and lithium ion battery
CN112448034A
